Productivity benefits of selectively breeding Black Tiger shrimp (Penaeus monodon) in Australia. (7th May 2015) - Norman‐Lόpez, Ana; Sellars, Melony J; Pascoe, Sean; Coman, Greg J; Murphy, Brian; Moore, Nick; Preston, Nigel
Abstract: Advances in the domestication and selective breeding of Australian Black Tiger shrimp, Penaeus monodon, opens the opportunity for world producers to reconsider the benefits of farming this species. Just over a decade ago this species was the world's most farmed shrimp species, however, difficulty in its domestication, in part, led to the widespread establishment of Penaeus vannamei (Pacific White shrimp) as the most farmed shrimp species in the world. This study empirically evaluates the productivity benefits of commercially domesticating P. monodon against production from wild broodstock of the same species. The evaluation compared the relative production from commercial ponds stocked with the progeny of wild P. monodon broodstock and ponds stocked with the progeny of domesticated stocks. The production data were from 164 ponds of domesticated stocks and 30 ponds of wild stocks, collected over 4 years (2009–2013) from two separate farm sites of the same Australian shrimp farming company. The wild stocks were sourced from the east coast of Australia. The results suggested that the productivity of the selectively bred stocks was 39% greater compared with production from wild stocks given equivalent amounts of feed and other inputs. Furthermore, productivity was additionally enhanced depending on the choice of feeds and whether stocking took place in September rather than later in the year (i.e. in early spring rather than late spring/early summer in the Southern hemisphere). This suggests that there is significant potential to further enhance the productivity of P. monodon farms via integrating advances in domestication, feeds and management practices.